Business Warriors: Unleashing the Power of Your Entrepreneurship Ideas - UiTM, Faculty of Business and Management (UiTM, 2023)
In an exciting entrepreneurial endeavor, the collaborative efforts of students from Entrepreneurial Strategic Management (ENT706) and International Entrepreneurship (ENT709) culminate in a seminar entitled "Business Warriors: Unleashing the Power of Your Entrepreneurship Ideas". Set to unfold on July 5th, 2023, from 9:00 a.m. to 1:00 p.m. at DK1 PFI FBM, UiTM Puncak Alam, the event proved to be an enlightening exploration of entrepreneurial strategies. Driven by the vision of Dr. Gouri Domnic Jacob and Dr. Janiffa Saidon, the seminar brought together 180 enthusiastic undergraduates eager to delve into the dynamic realm of business prowess.